Relationship of obesity, low-density lipoprotein cholesterol and myocardial perfusion in patients with risk factors and without atherosclerotic cardiovascular diseases - V. B. Sergienko; A. A. Ansheles; I. V. Sergienko; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2021)
Aim. In the retrospective study, to identify the relationship between body mass index (BMI), low-density lipoprotein cholesterol (LDL-C) levels and myocardial perfusion in patients without established atherosclerotic cardiovascular diseases.Material and methods. The study included 534 patients with cardiovascular risk factors but without established coronary artery disease, diabetes, myocardial infarction or coronary revascularization. In 76 of them, stress/rest myocardial perfusion single-photon emission computed tomography (SPECT) was performed.Results. The relationship between BMI and LDL-C levels is described by a quadratic (r2=0,21, p<0,001) function or a linear spline kinked in BMI of 27 kg/m2 (r=0,51, -0,46 — before and after this value, respectively; p<0,001). According to SPECT, focal stable and transient left ventricular myocardial perfusion abnormalities were not detected. However, there was a direct linear correlation between the heterogeneity of rest myocardial perfusion (ohet) and BMI (r=0,43, p<0,001), ohet and waist circumference (r=0,40, p<0,001), as well as between ohet and LDL-C (r=0,44, p<0,001).Conclusion. The relationship between BMI and LDL-C levels can be explained by endocrine dysfunction of adipose tissue, which disturbs the synthesis and metabolism of atherogenic lipoproteins. Obesity and increased LDL-C levels affect myocardial perfusion both by aggravating coronary atherogenesis and by microcirculatory disorders. Rest myocardial perfusion SPECT can be a method of screening for myocardial disorders caused by both diffuse atherosclerosis and metabolic syndrome.